A novel heterogeneous hybrid by incorporation of Nb2O5 microspheres and reduced graphene oxide for photocatalytic H2 evolution under visible light irradiation. Issue 58 (25th June 2015) - Yue, Zongkuan; Chu, Dongmei; Huang, Hui; Huang, Jie; Yang, Ping; Du, Yukou; Zhu, Mingshan; Lu, Cheng
<x xml:space="preserve">Abstract</x> A novel heterogeneous hybrid composed of Nb2O5 microspheres and reduced graphene oxide as photocatalyst exhibits superior photocatalytic activity and stability.